Pretty, Petite, Polite Dawn: Beauty Pageants, Housewifery and the Feminine Mystique in Philip Roth’s American Pastoral - Diogo Oliveira, (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
This article studies gender roles in Philip Roth’s American Pastoral, published in 1997. It addresses the housewife condition in 1960s America through the character of Dawn Dwyer, drawing from Betty Friedan’s The Feminine Mystique, published in 1963, and the second edition of Silvia Federici’s Revolution at Point Zero: Housework, Reproduction, and Feminist Struggle, published in 2020. Moreover, it analyses how American history is told and fictionalized in Roth’s work, comparing the scenes from the novel to Friedan’s non-fiction narrative of the 1960s. This analysis builds on previous works on gender roles in Roth’s literature, aiming to contribute to the body of literature on the American celebrated author.